Development of the contemporary concept of restorative justice: Towards increased visibility of crime victims - Ćopić Sanja (Temida)
Contemporary concept of restorative justice emerged at the end of 1960s and the beginning of 1970s, at the time when repression and social exclusion stared to show their lacks. Restorative justice has emerged on the critics of the conventional criminal justice response to crime, which denies the power to both the victim and the offender, and particularly neglecting a victim and minimizing his/her role in the procedure. While the accent of the repressive discourse is on the crime and punishment, restorative discourse is focused on the relationship between parities involved in a criminal case, who should actively participate in the process of finding out adequate solution of the problem arose from the criminal offence. Keeping that in mind, it is quite obvious that theoretical knowledge, concepts and movements that are focused on victims, their rights, legal and overall position had the strongest impact on the development of restorative justice. Taking that as a departure point, the impact of the “conflict as property” concept, victimology, movement for the restitution, movement for victim’s rights, and feminist movement, on the development of a contemporary concept of restorative justice is analyzed in this paper, and vice versa.